THE USE OF JAWS TO ENHANCE INFORMATION LITERACY CONCERNING THE BLIND COMMUNITY IN PERTUNI SEMARANG - Safii, Moh; Dewi, Amalia Nurma (2018)
The information era has changed the role of information literacy in the society. Being literate in this era means that a person holds power to change and enhance his/her life quality; this means that information literacy should be a basic right - that every person should have equal access to acquire it, including people who have special needs due to, for example, visual impairment. Visually impaired people have limited access to information, especially information in text form. Even though visually impaired people can use braille to gather information, the process of transforming information into the braille format fails to follow the rapid production and use of information in the information era. This condition has caused people with visual impairment to have a lower level of information literacy. To solve this problem Ted Hunter invented in 1989 a screen reader called JAWS and the reader has been continually improved since then. The JAWS screen reader is used worldwide to help people with visual impairment enhance their access to information, and the screen reader is also used by the blind community named Dewan Perwakilan Wilayah Persatuan Tunanetra Indonesia Semarang (DPW Pertuni). However most of the members of the DPW Pertuni Semarang community are not familiar with the technology, therefore this research aims at evaluating the impact of the JAWS Software concerning the level of information literacy of the Pertuni members. From our research we find that JAWS helps the members of the Pertuni community enhancing their information literacy, however, it is not all of the members.Rather, the majority of the group needs more than just technology; technology helps to increase the access, but it cannot motivate the members of the community to level up his/her motivation concerning their behavior toward information and not able to increase their critical thinking ability.